2002
DOI: 10.1051/vetres:2002016
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen binding in hypoxaemic calves

Abstract: -Blood oxygen transport and tissue oxygenation were studied in 28 calves from the Belgian White and Blue breed (20 healthy and 8 hypoxaemic ones). Hypoxaemic calves were selected according to their high respiratory frequency and to their low partial oxygen pressure (PaO 2 ) in the arterial blood. Venous and arterial blood samples were collected, and 2,3-diphosphoglycerate, adenosine triphosphate, chloride, inorganic phosphate and hemoglobin concentrations, and pH, PCO 2 and PO 2 were determined. An oxygen equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
3
2
0
2
Order By: Relevance
“…Regarding to blood gases blood pH is a biochemical indicator which must be between narrow intervals (7.2-7.6) for the tissue to perform in the body and affect the body functions negatively and even causes death (Karademir et al, 2001). Results of diseased calves showed significant decrease of pH, PO 2 and SO 2 together with significant increase in PCO 2 , HCO 3 and tCO 2 levels these results agree with Cambier et al, (2002) who reported that, blood oxygen levels binding in hypoxic calves PO 2 were investigated they showed that diseased animals exhibited a significant acidosis in arterial and venous blood. Also, our results of decrease in pH supported by (Cambier et al, 2002 andOk et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding to blood gases blood pH is a biochemical indicator which must be between narrow intervals (7.2-7.6) for the tissue to perform in the body and affect the body functions negatively and even causes death (Karademir et al, 2001). Results of diseased calves showed significant decrease of pH, PO 2 and SO 2 together with significant increase in PCO 2 , HCO 3 and tCO 2 levels these results agree with Cambier et al, (2002) who reported that, blood oxygen levels binding in hypoxic calves PO 2 were investigated they showed that diseased animals exhibited a significant acidosis in arterial and venous blood. Also, our results of decrease in pH supported by (Cambier et al, 2002 andOk et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Results of diseased calves showed significant decrease of pH, PO 2 and SO 2 together with significant increase in PCO 2 , HCO 3 and tCO 2 levels these results agree with Cambier et al, (2002) who reported that, blood oxygen levels binding in hypoxic calves PO 2 were investigated they showed that diseased animals exhibited a significant acidosis in arterial and venous blood. Also, our results of decrease in pH supported by (Cambier et al, 2002 andOk et al, 2005). The lung helps regulate pH in the body by exhaling carbon dioxide and in severe acidosis, there is rapid respiration in an effort to exhale more CO 2 in an effort to correct the imbalance (Montgomery, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…A correlation (r 2 =87.5%) between pCO 2 in arterial and venous blood was found by Gunes and Atalan (2006) in clinically healthy cross-bred calves. In this study, pCO 2 mean values were lower in all the periods than the 7.13 ± 0.84 kPa reported by Cambier et al (2002). This result suggests the absence of respiratory alkalosis and supports the hypothesis that pH increase could be caused by the diet administered.…”
Section: Discussionsupporting
confidence: 87%
“…De aquí que el Cly el P inorgánico podrían ser usados para incrementar la eficiencia del transporte del O 2 en animales hipóxicos (Gustin et al 1994), ya que la afinidad del O 2 a los glóbulos rojos puede ser modulada por adición y sustracción de iones Cl - (Bucci et al 1988). No obstante, la liberación de O 2 de la sangre se puede deteriorar en terneros con diarrea dependiendo del efecto de la enfermedad sobre ciertas variables en la bioquímica sanguínea (Cambier et al 2001), pues la acidosis in vivo y la hipercapnia, inducen una disminución en la afinidad del O 2 a la Hben la sangre arterial, la cual, se combina a la disminución en PaO 2 conduciendo a un grado de saturación de Hb -, en el compartimiento arterial (Cambier et al 2002).…”
Section: Sistemas Reguladoresunclassified